2014
DOI: 10.1093/nar/gku700
|View full text |Cite
|
Sign up to set email alerts
|

RNA recognition and self-association of CPEB4 is mediated by its tandem RRM domains

Abstract: Cytoplasmic polyadenylation is regulated by the interaction of the cytoplasmic polyadenylation element binding proteins (CPEB) with cytoplasmic polyadenylation element (CPE) containing mRNAs. The CPEB family comprises four paralogs, CPEB1–4, each composed of a variable N-terminal region, two RNA recognition motif (RRM) and a C-terminal ZZ-domain. We have characterized the RRM domains of CPEB4 and their binding properties using a combination of biochemical, biophysical and NMR techniques. Isothermal titration c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
(41 reference statements)
2
15
0
Order By: Relevance
“…No association of Musashi1 was observed with GST tagged BRaf (an activator of MAP kinase signaling, [ 87 ]), demonstrating specificity of the Musashi1:Musashi1 and Musashi1:CPEB interactions. Our analyses also revealed CPEB1:CPEB1 and CPEB4:CPEB4 homodimer formation ( Figure 3 B, left and right panels, respectively), consistent with prior findings [ 88 , 89 ]. Interestingly, we also observed CPEB1:CPEB4 heterodimers ( Figure 3 C), further adding to the range and complexity of mRNP formation between distinct RBPs.…”
Section: Experimental Evidence For Adaptive Regulatory Assemblies supporting
confidence: 92%
“…No association of Musashi1 was observed with GST tagged BRaf (an activator of MAP kinase signaling, [ 87 ]), demonstrating specificity of the Musashi1:Musashi1 and Musashi1:CPEB interactions. Our analyses also revealed CPEB1:CPEB1 and CPEB4:CPEB4 homodimer formation ( Figure 3 B, left and right panels, respectively), consistent with prior findings [ 88 , 89 ]. Interestingly, we also observed CPEB1:CPEB4 heterodimers ( Figure 3 C), further adding to the range and complexity of mRNP formation between distinct RBPs.…”
Section: Experimental Evidence For Adaptive Regulatory Assemblies supporting
confidence: 92%
“…In order to characterize the presence of complexes of different stoichiometries, we applied Ion Mobility-Mass Spectrometry (IM-MS) since this technique is valuable to detect the populations of different protein complexes at concentrations used in ITC experiments 7 16 . The analysis of the IM-MS data revealed the presence of monomeric species in the apo Pin1 form ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CPEBs also contain a protein-protein interaction site located at the N-terminus, which is highly divergent among the different members of the family. The RNA binding characteristics of CPEB1 and CPEB4 have been recently characterized to atomic detail 7 8 . The structural information has revealed that efficient recognition of the CPE sites is achieved using the pair of RRM domains working as a team, increasing the specificity by augmenting the protein-binding surface.…”
mentioning
confidence: 99%
“…Of these RNA-binding proteins, cytoplasmic polyadenylation element binding protein (CPEB) family are sequence-specific RNA-binding proteins and the key factors controling the elongation of the poly(A) tail and polyadenylation-induced translation (2,5,6). CPEB binds the cytoplasmic polyadenylation element (CPE) in the 3' untranslated regions of responding mRNAs (2,(7)(8)(9). CPEB-mediated effects on translation require at least two CPEs separated by less than 50 nucleotides in the target mRNA, which indicates the formation of CPEB-dimer (10).…”
Section: Translation and Cytoplasmic Polyadenylation Element Binding mentioning
confidence: 99%
“…All CPEB proteins have a similar structure with the C-terminal regions composed of two RNA recognition motifs (RRMs) and two zinc-fingercontaining sequence-specific RNA-binding proteins, as well as a regulatory N-terminal region (1,9,12). The N-terminals of CPEB1-4 are highly variable, whereas the C-terminals are more conserved (1).…”
Section: Translation and Cytoplasmic Polyadenylation Element Binding mentioning
confidence: 99%